2023
DOI: 10.1177/00221465221150283
|View full text |Cite
|
Sign up to set email alerts
|

Ongoing Remote Work, Returning to Working at Work, or in between during COVID-19: What Promotes Subjective Well-Being?

Abstract: The COVID-19 pandemic precipitated a massive turn to remote work, followed by subsequent shifts for many into hybrid or fully returning to the office. To understand the patterned dynamics of subjective well-being associated with shifting places of work, we conducted a nationally representative panel survey (October 2020 and April 2021) of U.S. employees who worked remotely at some point since the pandemic (N = 1,817). Cluster analysis identified four patterned constellations of well-being based on burnout, wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 58 publications
1
14
0
Order By: Relevance
“…In contrast, Bernstein et al (2020) found a reduction in stress among U.S. professional workers who TWFH, except among those with childcare obligations. This is similar to Fan and Moen's (2023) finding that the benefits of continued remote work during the pandemic were diminished among both men and women with caregiving obligations. Other studies have found distinctly gendered differences among caregivers who TWFH.…”
Section: Change and Stability In Work Location And Mental Healthsupporting
confidence: 84%
See 2 more Smart Citations
“…In contrast, Bernstein et al (2020) found a reduction in stress among U.S. professional workers who TWFH, except among those with childcare obligations. This is similar to Fan and Moen's (2023) finding that the benefits of continued remote work during the pandemic were diminished among both men and women with caregiving obligations. Other studies have found distinctly gendered differences among caregivers who TWFH.…”
Section: Change and Stability In Work Location And Mental Healthsupporting
confidence: 84%
“…This finding aligns with recent studies that have shown mixed results when it comes to the role the age of the youngest child in the household played during the pandemic, with some finding a reduced levels of work-family conflict among parents with teenage children (Schieman et al 2021), and others finding no effect of the age of children on parents’ psychological distress (Montazer et al 2022). Likewise, Fan and Moen (2023) found fewer benefits of longer-term remote work during the pandemic for both men and women with any caregiving obligations and some benefits (in terms of job and life satisfaction) of a return to work for women with care responsibilities, regardless of the child’s age. That said, at the time of our survey, 48 percent of workers in our sample who TWFH and had a preschool-aged child were using a daycare/preschool regularly, while only 17 percent of workers who TWFH and had a school-aged child had full access to in-person K-12 instruction.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…For example, a research placement may be delivered 80% remotely for activities related to research project preparation and 20% in‐person for data collection. This is a representation of hybrid working patterns, which provides benefits to workers' well‐being and may help to minimize burnout [ 17 ]. An agreed remote activity content is normally required between the placement provider, the learner(s) and the university's podiatry placement team prior to the start of a placement.…”
Section: The University Of Brighton Modelmentioning
confidence: 99%
“…schools resulted in a learning deficit (14). Closure of services and transition to remote work deteriorated health in certain communities (15)(16)(17)(18)(19).…”
mentioning
confidence: 99%